DIVA - Digital Identity in VANETs: A multi-authority framework for VANETs - Zaidi, Kamran; Rahulamathavan, Yogachandran; Rajarajan, Muttukrishnan (Proceedings - IEEE International Conference on Networks, 2013)
Vehicular ad hoc networks (VANETs) are the future of vehicular technology and Traffic Information Systems. The most important issue being looked into VANETs nowadays is that of security and privacy of vehicles and users. The current and past research has focused on using or securing the identity of vehicles in the network. However, in reality the vehicle's identity is not particularly useful for the authorities. Therefore, we present a novel idea for Digital Identity in VANETs that makes it more reliable and useful for both the authorities and the driver while providing the required level of security and privacy. Our scheme offers incentives for users and authorities to become part of VANETs thus helping in the deployment of the infrastructure.